Change in the international system and centers of global power- Future vision - - Mohamed Myaser Fattahi (Tikrit Journal For Political Science, 2015)
The change of the most prominent phenomena that hinder pathways and reactions of the international system. Through their impact on the interactive structure and building in addition to the units performances. The change caused by events and changes taking place in the domestic and regional environments as well as the international environment which caused the motives and in-centives directed movement of change towards a new internation-al environment، which sponsored by global forces are willing to change in an effort to ensure the interests and objectives addition-ally the expression of their capabilities and impact in the man-agement of international interactions and guidance. Thus، any at-tempt to explore the future of the international system must be preceded by an analysis of the nature of the change and the vari-ables that constitute movement for change and the forces acting in the system.